2001
DOI: 10.1159/000054688
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nitric Oxide in the Regulation of Growth Hormone Secretion in Dogs

Abstract: Nitric oxide (NO) is a highly reactive gas that has been suggested to function as a neurotransmitter in the neuroendocrine system. In this work, we have evaluated the role of NO pathways in growth hormone (GH) secretion by assessing the effect of L-arginine infusion, a precursor of NO formation, and L-NAME, a nitric oxide synthase (NOS) inhibitor. The experiments were carried out on 7 adult beagle dogs. A saline infusion was carried out on all the dogs as a control test. L-arginine (infusion i.v. 10 g in 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
3
18
0
1
Order By: Relevance
“…Similarly, the releasing activity of GHRP-6 has been proven NO dependent in dogs [36]. In good agreement with these results, our data show that the stimulatory effect of ghrelin requires the presence of NO; it is blocked by pretreatment with NAME, an inhibitor of NO synthases.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the releasing activity of GHRP-6 has been proven NO dependent in dogs [36]. In good agreement with these results, our data show that the stimulatory effect of ghrelin requires the presence of NO; it is blocked by pretreatment with NAME, an inhibitor of NO synthases.…”
Section: Discussionsupporting
confidence: 89%
“…NO donors show an inhibitory effect on GH secretion, probably because they release high nitrite levels [14]. In addition, NO inhibition may act by increasing the hypothalamic somatostatinergic tone and blunting endogenous GHRH secretion [27]. Hall and Garthwaite [28] reported that physiological NO concentration ranged to be 100 pM (or below) up to approximately 5 nM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that pituitary iNOS activation decreases GH secretion, since its inhibition by L-N(6)-(l-iminoethyl)lysine administration prevents the inhibitory effect of IFN-␥ on GH release in pituitary cell cultures (45). However, other data in the literature suggest that NO has a stimulatory effect on GH release in vitro (3,34), and in vivo (43). These discrepancies have been explained by a biphasic action of NO on GH secretion: a positive effect at low concentrations and a negative effect at high concentrations (7).…”
Section: Discussionmentioning
confidence: 99%